The magnetostratigraphy and cyclostratigraphy age data, and MS and NGR data used in cyclostratigraphy analyses of IODP Site 368-U1505 - Nie, Yunfeng; Wu, Huaichun; Satolli, Sara; Ferré, Eric; Shi, Meinan; Fang, Qiang; Xu, Ye; Zhang, Shihong; Li, Haiyan; Yang, Tianshui (PANGAEA, 2023)
The IODP Expedition 368 began drilling in the South China Sea in 2017. The initial chronology of Site 368-U1505, including magnetostratigraphy and biostratigraphy, was completed by the onboard scientists. This dataset includes the results of the onshore work of magneto-cyclostratigraphy and the raw data, the linear interpolated data, and detrended data of MS and NGR used for Cyclostratigraphy Analyses. Paleomagnetic samples (~8 cm³) were collected with a resolution of ~0.1-0.5 m from the upper ~200 m of Hole 368-U1505C and 368-U1505D, using nonmagnetic box. The raw data of geophysical records, including MS and NGR, were acquired during the expedition and downloaded from the IODP official website. These data are helpful to track the process of Cyclostratigraphy Analyses and provide a reference age datums with higher resolution compare to the onboard work. MS were measured nondestructively with the Whole-Round Multisensor Logger, while the Natural Gamma Radiation Logger measures the natural emission on whole-round cores using a system designed and built at the Integrated Ocean Drilling Program US Implementing Organization (USIO) (Texas A&M University). The magnetostratigraphy and cyclostratigraphy age data were obtained through comprehensive method. The magnetostratigraphic age framework was obtained through the stepwise demagnetizationof natural remanence, the calculation of declination and inclination of characteristic remanence by principal component analysis, and the comparison with GPTS. Cyclostratigraphic time-scale was obtained through Taner filtering of MS and NGR, Hilbert transform of the filtering results, and the comparison of the filtering curve and amplitude modulation with the theoretical astronomical solution. Progressive AF demagnetization was carried out using an ASC Scientific D-2000 AF demagnetizer. Remanent magnetization measurements after step-wise demagnetization, were performed with a 2G-755-4k cryogenic magnetometer. Filtering and Hilbert transform in time series analysisare completed using "Astrotron" R package, and the instructions are "tanner" and "testTilt", respectively.
Keywords: Cyclostratigraphy; Magnetic susceptibility; Magnetostratigraphy; Natural gamma ray; South China Sea